Remoção de fluoxetina por biossorção usando a microalga Chlorella vulgaris - Fernandes, Diana Alexandra Ferreira (2022)
Pharmaceuticals end up into the influent of municipal wastewater treatment plants (WWTPs). through the sewage system and due to the inability of conventional treatments to remove them, they are found on the environment. This work is focused on the contribution to the development of sustainable and economical tertiary treatments to remove pharmaceuticals in WWTPs.This study was developed within the scope of the international collaborative project REWATER, developed under the “Water Challenges for a Changing World Joint Program Initiative” (Water JPI). The microalga Chlorella vulgaris, live and dead, was used as biosorbent to remove a pharmaceutical that is consumed worldwide, fluoxetine, from aqueous solutions. Infrared spectroscopy characterization was made to living and lyophilized microalgae with and without being in contact with fluoxetine. This characterization allowed to identify the main functional groups, such as hydroxyl, sulfonic and carboxylic, that are probably involved in the biosorption process. The pH at the point of zero charge was 7.0 and 5.8 for living and dead microalgae, respectively. The study of the pH influence was performed. In relation to living microalgae, pH dependency was observed. As the initial pH increased, uptake adsorption of microalgae decreased. The reduction on the capacity was related to the pKa. The most favourable conditions for biosorption occur in pH range between 7.0 and 9.8 due to the electrostatic attraction between the positively charged fluoxetine and the negative charge alga surface. The effect of pH using lyophilized microalgae was inconclusive due to experimental problems. Adsorption of fluoxetine by microalgae was described by a pseudo-second order kinetics at room temperature (20-24°C). Lyophilized microalgae showed a higher kinetic constant, being the ones that achieved equilibrium first (15 min) and removed 55% of the initial fluoxetine. The kinetic constants were 3.4×10-4±1.3×10-4 and 5.4×10-4±1.3×10-4 gALGAE/(μgFLX·min), respectively for live and lyophilized microalgae. The equilibrium was reached by living microalgae within 20 min, for which 26% of fluoxetine was removed. Equilibrium studies revealed that this system followed the Langmuir model (at 20-24°C). A higher adsorption capacity was observed for living microalgae, suggesting that other mechanisms (e.g. metabolic processes) besides adsorption may contribute to fluoxetine removal. The maximum capacities were 1.9×103±0.1×103 and 1.6×103±0.2×103 μgFLX/gALGAE for living and dead microalgae, respectively. Although the microalga Chlorella vulgaris shows lower adsorption capacities than other adsorbents present in literature, its application is still promising due to their low cost, sustainability and in the case of lyophilized alga it is not affected by the presence of toxicants.